2022
DOI: 10.3390/su142316101
|View full text |Cite
|
Sign up to set email alerts
|

Reply to Fildani, A.; Hessler, A.M. Comment on “Gerbaudo et al. Are We Ready for a Sustainable Development? A Survey among Young Geoscientists in Italy. Sustainability 2022, 14, 7621”

Abstract: We very much appreciate and thank Andrea Fildani and Angela Hessler for their comment [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In our previous paper [26], illustrating the results of an investigation conducted among young Italian geoscientists on the links between ES and the UN 2030 Agenda, we found that the word "sustainability" is not prominent in the curricula of Italian Earth Sciences departments and that it is conceivable that most students would graduate without having taken a subject course focused specifically on how geosciences can tackle the SDGs and contribute to their fulfilment. Therefore, since it is our belief that the primary objective of the ES community is to put its very important and unique contributions on the floor of the public discussion via an educational program [27], it is crucial to investigate the role of Italian departments in disseminating sustainability education related to geoscience issues. Broadening the sample analyzed, to give voice not only to the young geoscientists, but also to the entire Italian geocommunity, we wanted to understand if the results confirm the vision of our previous study or whether, on the contrary, Italian Earth Sciences departments are fully aware of the environmental and ethical implications of their disciplines and of the fact that comprehension of the Earth's past is distinctly linked to a sustainable future for humanity.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper [26], illustrating the results of an investigation conducted among young Italian geoscientists on the links between ES and the UN 2030 Agenda, we found that the word "sustainability" is not prominent in the curricula of Italian Earth Sciences departments and that it is conceivable that most students would graduate without having taken a subject course focused specifically on how geosciences can tackle the SDGs and contribute to their fulfilment. Therefore, since it is our belief that the primary objective of the ES community is to put its very important and unique contributions on the floor of the public discussion via an educational program [27], it is crucial to investigate the role of Italian departments in disseminating sustainability education related to geoscience issues. Broadening the sample analyzed, to give voice not only to the young geoscientists, but also to the entire Italian geocommunity, we wanted to understand if the results confirm the vision of our previous study or whether, on the contrary, Italian Earth Sciences departments are fully aware of the environmental and ethical implications of their disciplines and of the fact that comprehension of the Earth's past is distinctly linked to a sustainable future for humanity.…”
Section: Introductionmentioning
confidence: 99%